2010
DOI: 10.1111/j.1502-3885.2010.00173.x
|View full text |Cite
|
Sign up to set email alerts
|

Chironomids as indicators of the Holocene climatic and environmental history of two lakes in Northeast Greenland

Abstract: Schmidt, S., Wagner, B., Heiri, O., Klug, M., Bennike, O. & Melles, M. 2010: Chironomids as indicators of the Holocene climatic and environmental history of two lakes in Northeast Greenland. Boreas, 10.1111/j.1502‐3885.2010.00173.x. ISSN 0300‐9483. Two Holocene sediment sequences from arctic lakes on Store Koldewey, an island in Northeast Greenland, were investigated for fossil chironomid assemblages. A total of 18 and 21 chironomid taxa were identified in 290‐ and 252‐cm‐long sediment sequences from Duck Lake… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
47
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(60 citation statements)
references
References 66 publications
(141 reference statements)
7
47
1
Order By: Relevance
“…Evidence for the fidelity of chironomids as indicators of palaeotemperature at LCL agrees with previous studies concluding that temperature was likely the primary driver (in some cases probably via intermediary effects on lake chemistry and trophic status) of chironomid assemblage shifts in East Greenland through the Holocene (Wagner et al 2005;Schmidt et al 2011). In another relevant study, Medeiros et al (2015) concluded that secondary gradients are relatively unproblematic in chironomid-based temperature reconstructions from unproductive Arctic lakes.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Evidence for the fidelity of chironomids as indicators of palaeotemperature at LCL agrees with previous studies concluding that temperature was likely the primary driver (in some cases probably via intermediary effects on lake chemistry and trophic status) of chironomid assemblage shifts in East Greenland through the Holocene (Wagner et al 2005;Schmidt et al 2011). In another relevant study, Medeiros et al (2015) concluded that secondary gradients are relatively unproblematic in chironomid-based temperature reconstructions from unproductive Arctic lakes.…”
Section: Discussionsupporting
confidence: 87%
“…5). At the same time, several lines of evidence suggest that the period before 10 kawas characterized by low temperatures, dilute waters and low productivity: the cold stenotherm Oliveridia/Hydrobaenus was abundant; assemblages from this period are similar to those of the late Holocene at LCL and to modern assemblages from lakes~650 km north on Store Koldewey (Schmidt et al 2011); and OM and bioSiO 2 are very low in sediments from this period (<2% dry weight of each; Fig. At the same time, several lines of evidence suggest that the period before 10 kawas characterized by low temperatures, dilute waters and low productivity: the cold stenotherm Oliveridia/Hydrobaenus was abundant; assemblages from this period are similar to those of the late Holocene at LCL and to modern assemblages from lakes~650 km north on Store Koldewey (Schmidt et al 2011); and OM and bioSiO 2 are very low in sediments from this period (<2% dry weight of each; Fig.…”
Section: Palaeoenvironmental Proxy Datamentioning
confidence: 97%
See 1 more Smart Citation
“…The timing of retracted outlet glaciers from Flade Isblink coincides with a local chironomid‐based temperature maximum ~8–5 ka from Store Koldeway in Northeast Greenland (Schmidt et al . ) and the general pattern of Early to Middle Holocene warming in Greenland (Kaufman et al . ; Briner et al .…”
Section: Discussionmentioning
confidence: 99%
“…, b, in press; Schmidt et al . ; Bennike & Wagner , ). Only a few lacustrine records from North Greenland have been studied and most of them have poorly constrained chronologies, which complicate robust palaeoenvironmental reconstructions (Fredskild , ; Funder & Abrahamsen ; Olsen et al .…”
mentioning
confidence: 99%